2021
DOI: 10.47108/jidhealth.vol4.iss1.82
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 in Iraq: an estimated cost to treat patients at a private clinic

Abstract: The impact of the COVID-19 pandemic extended to health, social and economic aspects of human life. The international failure to combat this crisis has left many countries suffering under the influence of successive waves of the pandemic. In this report, we present a private medical clinic's experience dealing with the COVID-19 epidemic in Iraq. The adopted protocol to treat COVID-19 patients has briefly been discussed with an estimated cost of treatment in the private sector. We found that most COVID-19 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…(19). Of note, the COVID-19 pandemic did not affect the health only but its effects have been extended to the social and economic aspect therefore, many studies focused on estimating the cost of COVID-19 disease and its treatments to understand the impact on economic aspects (20,21). Other researches were studied the clinical effects of COVID-19 treatments, however, there is a paucity in studies conducted to understand and explain both cost and effectiveness of COVID-19 treatments.…”
Section: Iraqi Journal Of Pharmaceutical Sciencementioning
confidence: 99%
“…(19). Of note, the COVID-19 pandemic did not affect the health only but its effects have been extended to the social and economic aspect therefore, many studies focused on estimating the cost of COVID-19 disease and its treatments to understand the impact on economic aspects (20,21). Other researches were studied the clinical effects of COVID-19 treatments, however, there is a paucity in studies conducted to understand and explain both cost and effectiveness of COVID-19 treatments.…”
Section: Iraqi Journal Of Pharmaceutical Sciencementioning
confidence: 99%
“…Such an understanding would be useful in designing prevention strategies for the patients' categories at increased risk of severe forms of disease and in treating such patients more efficiently. At the same time, the design and implementation of specific preventive strategies for the patients at risk are essential, as it was shown that we could not control pandemics only through measures of isolation and quarantine, especially when dealing with a virus that can reappear in successive waves across the globe, due to its impressive registry of mutations [75][76][77][78]. Suppose we accept the ferritin causal roles in infections like COVID-19.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Most healthcare providers have contracted COVID-19 and become carriers of the infection in their environments [17]. The increased workload and the absence of the necessary legal legislation to protect HCPs forced many of them to leave work due to the repeated occurrence of workplace violence by patients and their relatives [18]. The rumors about the coronavirus's source and the lack of benefit from receiving the vaccine reduced the rate of receiving the vaccine among the general Iraqi society.…”
Section: Introductionmentioning
confidence: 99%